Optimism, Social Intelligence and Positive Affect as Predictors of University Students’ Life Satisfaction - Rezaei, Akbar; Khosroshahi, Jafar Bahadori (European Journal of Mental Health, 2018)
The purpose of the present study was to investigate the relationship between optimism, social intelligence, and positive affect with students’ life satisfaction. The sample included 332 students of humanities sciences (213 females and 119 males) from Payame Noor University–Tabriz branch, who were randomly selected using stratified and multiple-stage cluster sampling. Extended Life Orientation questionnaire, Tromso Social Intelligence questionnaire, Positive affect and life satisfaction scales were used as data collection instruments and the data were analysed by Pearson’s correlation and hierarchical multiple regression analysis. The results of Pearson’s correlation analysis indicated a positive and meaningful correlation between social information processing, social skills, optimism, positive affect, and life satisfaction. Furthermore, the results of hierarchical multiple regression analysis also indicated the direct effect of social information processing and social skills on life satisfaction that later disappeared when optimism and positive affect were introduced in the second step. In the final model, only measures of optimism and positive affect were statistically meaningful. Therefore, social intelligence and positive affect promote (past tense?) life satisfaction in university students.